Screen-printed p-CdTe layers for CdS/CdTe solar cells - Klad'ko, V.P.; Lytvyn, P.M.; Osipyonok, N.M.; Pekar, G.S.; Prokopenko, I.V.; Singaevsky, A.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Correlation of the recrystallization process technological parameters with the morphology and structure of screen-printed p-CdTe layers intended for CdS/CdTe solar cell fabrication has been established. The optimal regimes to form layers with required characteristics have been found. As distinct from the used previously screen-printing techniques for CdS/CdTe solar cell fabrication, CdTe layers were doped with Ag or Au not by their diffusion from the layer surface but in the course of layer preparation. For this purpose, tellurides of those metals were added into the raw paste used for CdTe screen printing. It is shown that the developed method has some advantages and allows to prepare CdTe films, structural and electrophysical parameters of which are suitable to fabricate CdS/CdTe solar cells.